The Integration of “Project-Based” Teaching into the Curriculum - Shelton, Dale (Improving University Science Teaching and Learning, 2023)
The aim of this project was to evaluate the project-based course “Theme Projects: Experimental Molecular Biology” from both the students’ and supervisors’ perspectives and determine components which function suboptimally and can be improved upon in future blocks. Surveys were distributed to both students and supervisors enquiring about different aspects of the projects. The student survey was designed not only to get a general insight into the course but also to get the students to elaborate on comments in the official course evaluation and made in casual conversation during the projects. Whilst some comments made on the official evaluation did not appear to be a general problem for the course both students and supervisors alike see the integration of “Ethics” into the final project as problematic. Overall the course received good evaluations with most students being highly satisfied and willing to consider continuing research in their project area and supervisors willing to participate again next year.